Melanoma incidence in Australian commercial pilots, 2011–2016. Issue 7 (21st May 2019) - Olsen, Catherine M; Miura, Kyoko; Dusingize, Jean Claude; Hosegood, Ian; Brown, Russell; Drane, Michael; Clem, Peter; Marsden, Jerry; Tinker, Rick; Karipidis, Ken; Coroneo, Minas; Green, Adele C
Abstract : Objectives: Occupational exposure to cosmic and ultraviolet radiation may increase airline pilots' risk of cutaneous melanoma. Meta-analyses of available data show a higher than average incidence of melanoma in airline pilots, but the most recent systematic review revealed that few contemporary data are available. Moreover, all relevant studies have been conducted in Northern Hemisphere populations. We therefore aimed to examine if Australian commercial pilots have a raised incidence of melanoma compared with the general population. Methods: We examined all melanoma histologically diagnosed among Australian-licensed commercial pilots in the period 2011–2016 by manually reviewing de-identified data in the medical records system of the Australian Civil Aviation Safety Authority. We estimated age-specific incidence rates and compared these with corresponding population rates using standardised incidence ratios (SIRs) as measures of relative risk. Expected numbers were calculated by multiplying age- and calendar period-specific person-years (PYs) with corresponding rates from the entire Australian population; 95% CI were calculated assuming a Poisson distribution of the observed cases. Results: In this cohort of Australian-licensed commercial pilots observed for 91 370 PYs, 114 developed a melanoma (51 invasive, 63 in situ). More than 50% of melanomas occurred on the trunk, and the predominant subtype was superficial spreading melanoma. The SIR for invasive melanoma was 1.20 (95% CI 0.89 to 1.55) and for melanoma in situ, 1.39 (95% CI 1.08 to 1.78). Conclusion: Australian-licensed commercial pilots have a modestly raised risk of in situ melanoma but no elevation of invasive melanoma compared with the general population.